Rural Land Certification in Ethiopia : Process, Initial Impact, and Implications for Other African Countries - Deininger, Klaus; Ali, Daniel Ayalew; Holden, Stein; Zevenbergen, Jaap (World Bank, Washington, DC, 2012)
Although many African countries have recently adopted highly innovative and pro-poor land laws, lack of implementation thwarts their potentially far-reaching impact on productivity, poverty reduction, and governance. The authors use a representative household survey from Ethiopia where, over a short period, certificates to more than 20 million plots were issued to describe the certification process, explore its incidence and preliminary impact, and quantify the costs. While this provides many suggestions to ensure sustainability and enhance impact, Ethiopia's highly cost-effective first-time registration process provides important lessons.